The Stylistic Study of the Persian Letters of Rasid Vatvat (Phonic, Vocabulary, Syntactic, Ideological and Ideological layers) - Zolfaghar Elami; Roghayeh Mousavi (مطالعات زبانی و بلاغی)
Rashid Vatvat is among the famous poets and writers of the sixth century and his Persian letters is one of the most brilliant examples of prose texts in the prose literature of his period. It is so prominent that in recognition of the individual style of writing, this period is so important. In this work he has provided a perfect structure with the use of bizarre word, similes, harmony and the harmony of form, content, and the order of the words. So he examines the style of his letters in the recognition of his intellectual, personality and artistic dimensions. On the other hand the study of different styles of authors and ports in the form of layered analysis is a new method that has developed the discussions of style more precise and more scientific. Therefore the purpose of this paper is to analyze and investigate the phonic, vocabulary, and syntactic layers of his Persian letters in an analytical descriptive way. In order to show the macro layers by dividing the layers into the layers of decomposition and analysis the use of text based music using abstract vocabulary, blazonry and highlighting of the words is the creative use of language elements (simile, metaphor  ,metonym), axial morality, visualization and conception in Persian letters as the main feature of the author's style.